(untitled) (Biocenosis, 2022)
The Guanacaste Conservation Area (GCA) in Costa Rica, has a sector called El Hacha, where certain spots are vulnerable to forest fires, mainly due to anthropogenic causes. These sites present a savannah ecosystem, where two work areas were selected for the purpose of this research: one affected and the other unaffected by fire. The predominant tree vegetation in these areas is the nance (Byrsonima crassifolia) with a total of 22 individuals and raspaguacal (Curatella americana) with 131 individuals, while the rest corresponds to herbaceous graminoids (HG). The HG reach a degree of coverage of 95, 4 % in the unburned site, while in the burned site, bare soil predominates by 79,0 %. Regarding physicochemical properties, it is observed that the highest calorific value is possessed by raspaguacal with 17, 2 ± 0, 6 KJ g-1, followed by nance and HG. In contrast, the HG have the greatest capacity to lose moisture. They spread the flames at a lower speed, both horizontally and vertically, but for a longer period and with a low level of opacity, compared to the tree components. The estimated fuel load of both sites corresponds to 9149 MJ m-2 in the unaffected site and 1650 MJ m-2 in the site affected by the fire, being HG the greatest fire contribution factor in the El Hacha sector.